Strategi Social Media Marketing WOM Finance dalam Mempromosikan Produk Cicil Logam Mulia MASKu - Rifan Rahmadian; Rini Rinawati (UNISBA Press, 2023)
Abstract. WOM Finance was founded in 1982. WOM Finance utilizes social media Instagram as its marketing strategy to promote MASKu's precious metal installment products. MASKu's precious metal installment product is a 24k precious metal (gold) financing service in installments/credit. MASKu is here as a solution in an effort to help and make it easier for people to own precious metals (gold). The purpose of this study was to determine the formulation, implementation, and evaluation of WOM Finance's social media marketing strategy in promoting MASKu's precious metal installment products. In this study using qualitative methods, with a case study approach. The results obtained indicate that in the formulation of the strategy there are objectives, identification and backup strategies. Then in implementing the strategy there is creating content, creating effective strategies, and utilizing information. The social media marketing strategy activities carried out by WOM Finance in promoting MASKu's precious metal installment products on Instagram with the aim of promoting the product have been fulfilled, in terms of better impressions and engagement. The purpose of selling gold has not been achieved. To improve the future strategy, there is a strategy evaluation activity by changing the posting schedule on Instagram. Abstrak. WOM Finance didirikan pada tahun 1982. WOM Finance memanfaatkan media sosial instagram sebagai strategi pemasarannya untuk mempromosikan produk cicil logam mulia MASKu. Produk cicil logam mulia MASKu merupakan layanan pembiayaan logam mulia (emas) 24k secara cicilan/kredit. MASKu hadir sebagai solusi dalam upaya membantu serta memudahkan masyarakat untuk memiliki logam mulia (emas). Tujuan penelitian ini untuk mengetahui perumusan, pelaksanaan, dan evaluasi strategi social media marketing WOM Finance dalam mempromosikan produk cicil logam mulia MASKu. Pada penelitian ini menggunakan metode kualitatif, dengan pendekatan studi kasus. Hasil yang diperoleh menunjukkan bahwa pada perumusan strategi terdapat tujuan, identifikasi, dan strategi cadangan. Kemudian pada pelaksanaan strategi terdapat pembuatan konten, menciptakan strategi efektif, dan memanfaatkan informasi. Kegiatan strategi social media marketing yang dilakukan WOM Finance dalam mempromosikan produk cicil logam mulia MASKu di instagramnya secara tujuan mempromosikan produk sudah terpenuhi, dilihat dari segi impression dan engagement yang lebih baik. Untuk tujuan jualan emas belum tercapai. Untuk memperbaiki strategi kedepannya maka terdapat kegiatan evaluasi strategi dengan melakukan perubahan jadwal posting di instagram.